INTERACTIVE TECHNOLOGIES IN TEACHING UZBEK FOLK MUSIC - Turdiboyeva Moxlaroy Adashbekovna (Web of Journals Publishing, 2024)
This article analyzes the importance and possibilities of using interactive technologies in teaching Uzbek folk music. The uniqueness and rich cultural heritage of Uzbek folk music can be effectively taught to students using new technologies. Interactive technologies, such as multimedia resources, mobile applications, virtual and augmented reality (VR/AR), music programs and online platforms, significantly revitalize the process of music education. With the help of these technologies, students will have the opportunity to virtually learn folk music instruments, consolidate music theory through games and tests, as well as share their performances. The article also shows that interactive technologies are an effective tool for studying not only the theoretical, but also the practical aspects of music. This approach ensures the complete and modern transmission of Uzbek folk music to future generations.
Keywords: Uzbek folk music, interactive technologies, music education, multimedia, mobile applications, virtual reality (VR), augmented reality (AR), online platforms, music theory, musical performance, musical instruments, teaching methodology, innovative education, interactive games, musical creativity, distance learning.